OPTIMIZATION OF TRAINING PROGRAM DEVELOPMENT FOR REMOTELY PILOTED AIRCRAFT OPERATORS IN THE SPHERE OF BORDER SURVEILLANCE (Revista Inclusiones, 2021)
The study reveals the theoretical and practical approaches of developing training programs forRemotely Piloted Aircraft operators in the sphere of border surveillance of the state border protectionagencies of the European Union and Ukraine using multicriteria optimization to find required rationalparameters. According to the developed methodology, using the multicriteria optimization methodprovides an opportunity to choose a program for training such specialists, which will best meet theobjectives and peculiar needs of the state border protection agencies of the European Union andUkraine. The results of the study within the educational grant of Frontex Agency conducted by theteam of experts from the Border Guard Services of Ukraine and EU countries were used to enhancethe training program of air reconnaissance units of border protection bodies at the Main TrainingCentre of the Border Guard Service of Ukraine based on the best EU practices, in order to ensureobtaining of knowledge and practical skills by personnel of the border guard Remotely Piloted Aircraftexternal crews, which will increase the level of interoperability and professional competence of borderguards while conducting border surveillance tasks.